Study for Cataclysm (Simbiótica. Revista Eletrônica, 2022)
The work “Study for cataclysm” consists of a mural painting presented in the exhibition “The melancholy of the Landscape” at the Sem Título Arte gallery in Fortaleza, Ceará. Curated by Efrain Almeida, the exhibition had its opening in August 2019, a few months before the onset of the coronavirus pandemic in 2020. Informed by the materiality of the paint used and the verticality of the wall where it was created, the mural-intervention painting, exposed to the strong sun of the city of Fortaleza, unravels as the days go by. Landscape - inscription that builds and deconstructs itself under our witness.